Potting media influence on root development of fig (Ficus curicuL.) - Shamsudin, Mohd Syufihuddin; Shahari, Rozilawati; Tajudin, Nur Shuhada; Che Amri, Che Nurul Aini; Mispan, Mohd Razali (2017)
This study aims to determine the eft'ect of potting media and type of cutting on root development of fig (Ficus carica L). fhe experiment was carried out at the Glasshouse and Nursery Complex (GNC), International Islamic Universit5, Mala-vsia (Iiulvf ). The experiment used a split plot design, u,'ith the main plot (potting media) and sub plot (cutting type). The potting rnedium used w-ere sand + topsoil (1 :3). topsoil + peat * sarvdust (1:i:1) and peat + perlite (1:1i. Trvo type of cuttings used r,vere serni-hardwood and hardwood cutting. The cuttings \\'ere collected every five da.vs interval rvithin two months (April to May 2017). The parameters observed were root mass, root emergence, no of primary root, number of secondary root. no of tertiar,v root, longest primary root length and longest secondary root length. As a result, peat + perlite (1 :1) with hardw.ood cutting type shows highest root growlh and development. It is recommended to Llse hardwood cufiing type with peat + perlite as potting media for fig propagation.